Coral Reef Fish and Plankton Diversity toward Coral Reef Coverage in Panjang Island of Anak Krakatoa Mountain - Gita Puspitasari; Endang Linirin Widiastuti; Henni Wijayanti; Tugiyono Tugiyono (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
The coral reef is part of the marine ecosystem that important because of its role as a source of life, especially for marine variety creatures. This study aims to determine the relationship of the diversity of reef fish and plankton to coral reef cover on the Panjang Island of Anak Krakatoa Mount, Lampung. Line Intercept Transect used for retrieval of coral reef data and the Underwater Visual Census method for collecting coral reef fish data. Diversity and dominance index are utilized to analyze correlations between them. A good coral reef is obtained at point 2 (5 meters in depth) while at other points the condition of the coral reef is classified as moderate. The highest number of fish is found at point 1 (5 meters in depth) with 56 individuals. The highest plankton diversity is 3.04 Index whereas located at point 2 (0 meters in depth). They have a positive correlation (0.955-coral reef coverage with fishes, 0.916-diversity of reef fish and coral reefs, 0.833-diversity of reef fish with plankton) upon their relationship.